Hubungan Konsumsi Kopi dan Kualitas Tidur Dengan Status Gizi Pada Mahasiswa Tingkat Akhir Teknik Sipil UNESA - Hamnie Zahra (Lembaga Pengembangan Kinerja Dosen, 2024)
Increased coffee intake and sleep quality can affect the body so that it can have side effects on changes in nutritional status. The purpose of this study was to analyze the relationship between coffee consumption and sleep quality with nutritional status in Civil Engineering students at UNESA. This research design is using cross sectional. Data collection using questionnaires and anthropometric measurements of height and weight. The subjects in this study amounted to 62 people. Analysis of the relationship between coffee consumption variables and sleep quality with nutritional status using Spearman Rank test analysis. The results showed that there were 5 (9,09%) underweight students, 35 (63,6%) normal nutritional status, and 15 (27.2%) overweight students. Coffee consumption habits are classified as low as 9 people (16.3%), moderate as many as 44 people (80%), and high as many as 2 people (3.6%). Sleep quality was in the bad category as many as 43 people (78,1%) and in the good category as many as 12 people (21,8%). This study shows that the relationship between coffee consumption and nutritional status (p=0.179) and the relationship between sleep quality and nutritional status (p=0.949). Consuming a good amount of coffee and quality sleep will not affect nutritional status. Other factors that influence nutritional status are physical activity and food intake. The conclusion of this research is that there is no relationship between coffee consumption and nutritional status or sleep quality and nutritional status in UNESA Final Year Civil Engineering students. It is recommended that data be heterogeneous so that it can be more varied and not homogeneous.